PARADIGMA BARU DALAM PENGELOLAAN ORGANISASI PENDIDIKAN MENUJU SISTEM MANAJEMEN BERBASIS ADAPTASI DAN KOLABORASI - Subandi, Muhammad; Suherman, Maman; Kurniawati, Nia; Khamim, Nur; Aji Fachrurroji, Fahmi (Penerbit Lafadz Jaya, 2025)
Changes in the management of educational organizations have become an urgent necessity in response to the increasing complexity of 21st-century challenges, technological advancements, and demands for educational quality. Many schools still implement static and bureaucratic management systems characterized by hierarchical structures, one-way communication, and minimal participation from school stakeholders. Such systems have proven ineffective in responding quickly and efficiently to change. This study aims to examine the transition of school management systems from a static approach to an adaptive and collaborative management model, as well as to analyze the role of school principals as agents of change in this process. The study employs a qualitative approach using a case study method at a Vocational High School (SMK) in West Java Province. The findings indicate that the transition to an adaptive and collaborative management system is achieved through transformational leadership by the principal, which encourages open communication, stakeholder involvement in decision-making, and the development of a collaborative culture. Organizational restructuring toward more flexible models and the use of information technology have also accelerated the adaptation process. Nonetheless, challenges persist in the form of resistance to change, limited resources, and administrative barriers. The study concludes that adaptation- and collaboration-based management can enhance school management effectiveness and strengthen stakeholder participation in building a responsive and innovative organizational culture.